Chum salmon egg extracts induce upregulation of collagen type I and exert antioxidative effects on human dermal fibroblast cultures - Yoshino A (Dove Medical Press, 2016)
Atsushi Yoshino,1 Natalia Polouliakh,1–3 Akira Meguro,1 Masaki Takeuchi,1,4 Tatsukata Kawagoe,1 Nobuhisa Mizuki1 1Department of Ophthalmology and Visual Science, Yokohama City University Graduate School of Medicine, Yokohama, Kanagawa, 2Sony Computer Science Laboratories Inc., Fundamental Research Laboratories, 3Systems Biology Institute, Tokyo, Japan; 4Inflammatory Disease Section, National Human Genome Research Institute, National Institutes of Health, Bethesda, MD, USA Abstract: Components of fish roe possess antioxidant and antiaging activities, making them potentially very beneficial natural resources. Here, we investigated chum salmon eggs (CSEs) as a source of active ingredients, including vitamins, unsaturated fatty acids, and proteins. We incubated human dermal fibroblast cultures for 48 hours with high and low concentrations of CSE extracts and analyzed changes in gene expression. Cells treated with CSE extract showed concentration-dependent upregulation of collagen type I genes and of multiple antioxidative genes, including OXR1, TXNRD1, and PRDX family genes. We further conducted in silico phylogenetic footprinting analysis of promoter regions. These results suggested that transcription factors such as acute myeloid leukemia-1a and cyclic adenosine monophosphate response element-binding protein may be involved in the observed upregulation of antioxidative genes. Our results support the idea that CSEs are strong candidate sources of antioxidant materials and cosmeceutically effective ingredients. Keywords: fish egg, antiaging, gene expression analysis, antioxidative gene, phylogenetic footprinting analysis